Genocias ir rezistencija Nr. 1(1) - Pocius, Mindaugas; Starkauskas, Juozas; Petravičiūtė, Inga; Tūtlis, Vidmantas; Janavičienė, Audronė; Streikus, Arūnas; Bubnys, Arūnas; Anušauskas, Arvydas (Genocidas ir rezistencija, 1997)
Pilnas leidinys (nuskenuota popierinė versija)